Cold gas spraying of copper and tin onto metallic and non metallic substrates - Calla, Eklavya (2005)
Cold gas dynamic spraying (CGDS) is a recent development in the field of thermal spraying in which a powder feedstock can be deposited onto a substrate to form a coating without it being heated significantly. The aim of the present study was to investigate the potential for manufacturing electrical circuits for automobile applications by depositing copper tracks on non-metallic substrates. Powders were sprayed using He gas at room temperature and elevated temperatures onto a number of different polymers, ceramic and metal substrates to understand the factors controlling deposit formation and the development of adequate adhesion between track and substrate. The use of tin as an interlayer to improve adhesion was a novel development in this study.